CLINICAL NURSING STUDENTS’ SELF CONFIDENCE DURING E-LEARNING IMPLEMENTATION - Made Satya Nugraha Gautama; Sugiarsih Sugiarsih; Totok Harjanto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: E-learning as a learning method with a flexible and interactive pedagogical approach has a positive impact on the value of self-confidence of nursing students. School of Nursing, Faculty of Medicine Public Health and Nursing Universitas Gadjah Mada (FMPHN UGM) develop e-learning for nursing students in clinical practice learning which requires an evaluation to e-learning implementation by describing the self-confidence of the nursing student after use e-learning. The purpose of this study was to describe self-confidence (SC) of the clinical nursing students based on 3 selfconfidence’s components that consist of cognitive, affective, and psychomotor.Methods: A Descriptive study with a cross-sectional design toward 95 clinical nursing students in the stage of nursing management and basic nursing practice in September 2018 period at the School of Nursing FMPHN UGM. Data analysis used the univariate analysis with descriptive statistic test to describe respondent characteristic and variable. Student Satisfaction and Self-Confidence in Learning Instrument by National League for Nursing (NLN) in 2005 was used in this study. The instrument was through cultural adaptation and modification first.Results: The self-confidence of nursing students as e-learning evaluation found that the majority of respondents (90,5%) had high levels of self-confidence. Components of self confidence, consist of cognitive, affective and psychomotor also showed that the majority of respondents were in the high category (84,2%; 88,4%; 66,3%).Conclusion: Clinical nursing students have high self-confidence after going through e-learning.